A selectivity switch for CO2 electroreduction by continuously tuned semi-coherent interface - Zhang, Tao (2024)
Mass production of Au–Cu-based catalysts with tailored selectivity is a complex and challenging task. We report a semi-affinity strategy to realize the synthesis of Au–Cu Janus nanocrystals with continuously tuned interfaces (from dimer, Janus, acorn-like Janus, to core-shell) based on Au nanosphere seeds. We highlight the role of interfacial strain due to a large lattice mismatch in growth control. The systematic electrochemical evaluation shows that the interfacial Cu oxide state, ∗CO coverage, and intermediate adsorption configuration can be well tuned by tailoring the Janus nanostructure. Optimized Au–Cu Janus catalyst reaches an efficiency of up to 80.0% for C2+ product with a partial current density of 466.1 mA cm−2. The reaction products can be selectively switched from methanol (dimer) to ethanol (Janus) and further to ethylene (acorn-like Janus) by increasing the interface area of the Au–Cu heterostructures. The catalytic mechanisms are unraveled by operando surface-enhanced Raman spectroscopy (SERS) analysis and density functional theory calculations.